ANALISIS KESEJAHTERAAN SUBJEKTIF GURU HONORER DI SEKOLAH DASAR DAN DAMPAKNYA PADA PELAKSANAAN PEMBELAJARAN DI MASA PANDEMI COVID – 19 - Nurjamaludin, Muhammad; Sifa, mila (Pendidikan Guru Sekolah Dasar Institut Pendidikan Indonesia Garut, 2021)
Based on the results of the study, it was found that the subjective well being level of honorary teachers was in the high category, namely (60%) meaning that they did not feel deprived in their life, one of the factors was due to other factors that were able to support their life needs such as the presence of a husband in their life. The impact of the learning process is that there is additional financial expenditure because the implementation of online teaching learning requires a large amount of funds. Not only teachers who feel the impact directly, students experience the same thing they have difficulty absorbing the material provided by the teacher because most of it is carried out through assignments. Then not all students do not have cellphones as a learning medium, then not all parents are able to accompany student learning so that delays in collecting assignments often occur